A binary-distributed effector modulates fungal host preference for drosophilids by targeting a lineage-specific immune factor - Yujuan Luo; Xinlu Sheng; Dongxiang Wei; Shuangxiu Song; Chen Chen; Hongyun Wu; Junmei Shang; Chengshu Wang (Proceedings of the National Academy of Sciences, 2025)
Unlike host-specific parasites, broad-spectrum pathogens often exhibit an enigmatic strain/race-level preference for infecting particular host species over others. Here, we identify a polymorphic effector (termed Bhe1) that exhibits a binary presence–absence distribution pattern among strains of the entomopathogenic fungus Beauveria bassiana . Gene deletion and overexpression in Bhe1- present strains revealed that this gene functions as a virulence factor against Drosophila species but dispensable for infection of mosquitoes, beetles, and locusts. Through targeted protein screening, we verified that Bhe1 targets a drosophilid-specific factor with an unknown function (termed Dsff1). The expression of Dsff1 is induced in Drosophila melanogaster upon fungal infection and is controlled by the Toll pathway. Survival of Dsff1 RNA interference (RNAi) flies was impaired after infection with the wild-type but not Δ Bhe1 strain of B. bassiana . Overexpression of Bhe1 and Dsff1 in D. melanogaster, respectively, suppresses and promotes fly antifungal immunity. Further investigations reveal that Dsff1 binds Bombardier (Bbd), and Bhe1 blocks their interaction. Consistent with Bbd’s role as a Toll-mediated immune factor, both Dsff1 and Bbd RNAi flies exhibit similar defects in the secretion of immune factors, including antifungal peptides. While revealing the mechanistic control of parasite host preference, our identification of a novel immune factor in Drosophila underscores a compelling instance of host–parasite evolutionary arms race.